"Las fuentes de la Constitución Nacional " como "fuente" de disputa (personal y no) académica - Mocoroa, Juan M. (2014)
In this paper, I will present a discussion which arose in the Argentinean doctrine about the identification of the sources of the Constitution. This topic, it is used as an excuse to think about the value of academic discussion in our country. To do this, I will use the confrontation between Dardo Pérez Ghilou, on one hand, and Manuel García Mansilla and Ricardo Ramirez Calvo, on the other. About the concrete discussion, I argue that it is based on an unfortunate misunderstanding. And which the outcome is a pity for the value of academic deliberation. In fact, it is argued that academic differences become personal offenses.